Sistema de georreferenciación para el análisis de producción científica de los docentes investigadores de la Universidad Técnica de Cotopaxi - Quisaguano Collaguazo, Luis René (2020)
The research professors of the Technical University of Cotopaxi in the development of their scientific studies require the timely collaboration of experts in specific areas that cannot be easily located because their location and the impact of their research work framed in areas are unknown. geographical boundaries, which is why the development of a georeferencing system for the analysis of scientific production using web development tools and the agile Scrum methodology is proposed. In chapter I a bibliographic review is made to define background, epistemology and the state of the art of concepts associated with software development and georeferencing. In addition, issues related to the analysis of scientific production, bibliometry, Scientometry, etc. are addressed. In Chapter II the necessary mechanisms are designed to solve the problem detected by applying field research techniques, in the same way the artifacts to be carried out to document the development process are defined, among them the product backlog and the sprint backlog stand out. Chapter III describes the results obtained from the application of the proposal for which the tabulation and analysis of the data collected through surveys is carried out, in the same way the validation is applied by the criteria of experts where the implementations made in the system are reviewed of georeferencing for the analysis of scientific production.